Performance Benchmarking of FHIR Terminology Operations in ETL Jobs - Wiedekopf, Joshua; Drenkhahn, Cora M.; Ingenerf, Josef (Studies in health technology and informatics, 2023)
Interoperability in healthcare cannot be achieved without mapping local data to standardized terminology. In this paper, we investigate the performance of different approaches for implementing HL7 FHIR Terminology Module operations using a benchmarking methodology, to gather evidence on the benefits and pitfalls of these methods in terms of performance from the point-of-view of a terminology client. The approaches perform very differently, while having a local client-side cache for all operations is of supreme importance. The results of our investigation show that careful consideration of the integration environment, potential bottlenecks, and implementation strategies is required.
Keywords: Benchmarking; Delivery of Health Care; Electronic Health Records; Health Facilities; Health Level Seven; Humans